NEW UZBEKISTAN IN THE CONTEXT OF GLOBALIZATION: GREAT GOALS AND KEY FEATURES OF MODERN SOCIETY DEVELOPMENT (Scientific journal of the Fergana State University, 2026)
This article provides a socio-philosophical analysis of the positive and negative impacts of globalization on the development of New Uzbekistan. Within the framework of the “New Uzbekistan” concept, the role of major goals-such as enhancing human dignity, preserving national identity, ensuring social justice, building a competitive economy, and creating a spiritually mature society-is examined in the context of global processes. The paper also scientifically substantiates the need to preserve national values, strengthen spiritual immunity, and harmoniously integrate advanced international experience into the national development strategy.